2023
DOI: 10.1539/eohp.2023-0009-oa
|View full text |Cite
|
Sign up to set email alerts
|

Job stress in a multinational corporation: cross-country comparison between Japan and Vietnam

Odgerel Chimed-Ochir,
Tatsuhiko Kubo,
Oyundari Batsaikhan
et al.

Abstract: Objective: The current study aimed to identify workplace stress and how stress factors differed in employees of a multinational company's subsidiaries in Japan and Vietnam. Methods: For the study, a total of 340 Japanese and 379 Vietnamese workers were included from their corresponding subsidiaries of a multinational company headquartered in Japan. The data were anonymously collected via an online pre-administered questionnaire between November 2021 and February 2022. A brief Job Stress Questionnaire was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Over the past three decades, the stress of employees on the job has gradually become a topic of increasing attention and has been comprehensively researched in the field of occupational health. According to Vietnam, a country with a rapidly developing economy, more and more occupational health problems are emerging in employees [1]. Many studies have shown that job stress has a negative impact on work performance [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, the stress of employees on the job has gradually become a topic of increasing attention and has been comprehensively researched in the field of occupational health. According to Vietnam, a country with a rapidly developing economy, more and more occupational health problems are emerging in employees [1]. Many studies have shown that job stress has a negative impact on work performance [2,3].…”
Section: Introductionmentioning
confidence: 99%